Challenges of interpreting the musculoskeletal manifestation of lymphoma: A case report. Issue 1 (February 2021) - Clary, D.; Ali, A.; Syed, I.
Abstract: Background: Primary Bone Lymphoma can be challenging to interpret even for the experienced reviewer. This case demonstrates the subtle multimodality appearances encountered. Case summary: a gentleman in his late 70s with one week history of groin pain underwent plain radiography and subsequent further imaging. Only following biopsy was the diagnosis of primary bone lymphoma made for which the patient has received successful treatment. Conclusion: This case demonstrates the difficulties in identifying lymphoma when seen within the musculoskeletal system. It also provides opportunity to reflect on the importance of initial imaging, good quality history and understanding of differentials.